Method for preparing waste liquid purification material using electrolytic manganese slag and phosphogypsum leachate and waste liquid purification material

By passing the electrolytic manganese slag and phosphogypsum leachate through hydrothermal reaction and carbonization, waste liquid purification materials are prepared, which solves the problem of electrolytic manganese slag and phosphogypsum leachate, and efficient removal of organic and heavy metal pollutants in the waste liquid is achieved, reducing environmental pollution and achieving high-value utilization of waste.

CN119075920BActive Publication Date: 2025-03-07CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411587351.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-07
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The treatment and utilization of electrolytic manganese slag and phosphogypsum leachate has always been a problem in the fields of environmental protection and resource utilization. It is difficult for the existing technology to effectively coordinate the treatment of these waste slag and waste liquid, resulting in environmental pollution and waste resources.

Method used

By mixing electrolytic manganese slag with iron-containing solid waste and stirring evenly, iron-manganese slag material is obtained; then mixing with fly ash and mud material, stirring evenly, granulating, aging, and obtaining raw material pellets; mixing waste leachate and phosphogypsum leachate, stirring evenly, obtaining hydrothermal liquid; immersing the raw material in the hydrothermal liquid, conducting hydrothermal reactions to obtain initial purification material; finally, carbonizing the initial purification material to obtain waste liquid purification material.

Benefits of technology

The prepared waste liquid purification materials can not only efficiently adsorb and degrade high-concentration organic pollutants in waste liquid, but also simultaneously remove heavy metal pollutants in waste liquid, reduce environmental pollution, and achieve high-value utilization of waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119075920B_ABST
    Figure CN119075920B_ABST
Patent Text Reader

Abstract

The present disclosure proposes a method and waste liquid purification material for preparing waste liquid purification materials using electrolytic manganese slag and phosphogypsum leachate, and belongs to the technical field of hazardous waste resource utilization. The method includes mixing electrolytic manganese slag and iron-containing solid waste, stirring evenly to obtain iron-manganese slag material; mixing iron-manganese slag material with fly ash and mud material, stirring evenly, granulating, aging, and obtaining raw material particles; mixing garbage leachate and phosphogypsum leachate, stirring evenly to obtain hydrothermal liquid; immersing the raw material particles in the hydrothermal liquid, performing a hydrothermal reaction, and obtaining an initial purification material by the hydrothermal reaction; carbonizing the initial purification material, and obtaining a waste liquid purification material after carbonization. The preparation process of the present disclosure is simple, and the required raw materials are all industrial wastes. Through reasonable batching, hydrothermal reaction and carbonization, the waste liquid purification material is prepared using electrolytic manganese slag and phosphogypsum leachate, which can not only efficiently adsorb and degrade high-concentration organic pollutants in the waste liquid, but also simultaneously remove heavy metal pollutants in the waste liquid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of resource utilization of hazardous wastes, and specifically relates to a method for preparing a waste liquid purification material by utilizing electrolytic manganese slag and phosphogypsum leachate, and the waste liquid purification material. Background Art

[0002] The treatment strategy of electrolytic manganese slag is refined into three core levels: safe storage management, harmless transformation treatment and efficient resource utilization. At the technical level, it is further refined into four major technical paths: safe storage technology system, dry treatment technology, pyrothermal treatment technology and wet treatment technology. Among them, the harmless transformation strategy is particularly rich, covering the use of cement solidification technology to stabilize manganese slag, chemical solidification / stabilization treatment, as an additive in cement production, the preparation of unburned brick materials, and even new applications in agricultural fertilizers.

[0003] As an important by-product of phosphate fertilizer production, phosphogypsum is not only large in volume, but also contains complex chemical components, including a series of heavy metal elements and fluoride ions, phosphate ions, and sulfate ions. The liquid seeping from phosphogypsum will cause environmental pollution to surface and groundwater bodies. For the treatment of phosphogypsum reservoir leachate, innovative value-added processes must be designed and implemented to promote the recycling of resources and reduce adverse impacts on the environment.

[0004] Electrolytic manganese slag and phosphogypsum leachate are both waste slag and waste liquid generated in the industrial production process. Their treatment and utilization have always been a difficult problem in the field of environmental protection and resource utilization. Therefore, it is necessary to propose a method for the coordinated treatment of electrolytic manganese slag and phosphogypsum leachate. Summary of the invention

[0005] The present disclosure aims to solve at least one of the technical problems existing in the prior art, and provides a method for preparing a waste liquid purification material using electrolytic manganese slag and phosphogypsum leachate, and a waste liquid purification material.

[0006] In one aspect of the present disclosure, there is provided a method for preparing a waste liquid purification material using electrolytic manganese slag and phosphogypsum leachate, the method comprising:

[0007] The electrolytic manganese slag and the iron-containing solid waste are mixed and stirred evenly to obtain an iron-manganese slag material;

[0008] The ferromanganese slag is mixed with fly ash and mud, stirred evenly, granulated, aged to obtain raw material pellets;

[0009] The landfill leachate and the phosphogypsum leachate are mixed and stirred evenly to obtain a hydrothermal solution;

[0010] Immersing the raw material particles in the hydrothermal liquid to perform a hydrothermal reaction, and after the hydrothermal reaction is completed, taking out the solid part to obtain an initial purified material;

[0011] The initial purification material is carbonized, and the waste liquid purification material is obtained after the carbonization is completed.

[0012] Optionally, the mass ratio of the electrolytic manganese slag to the iron-containing solid waste is (15~75):100.

[0013] Optionally, the iron-containing solid waste is any one of blast furnace gas mud, blast furnace gas ash, converter dust mud, electric furnace dust, and steel rolling dust mud.

[0014] Optionally, the mass ratio of the ferromanganese slag to fly ash and mud is (20-60):(15-45):100.

[0015] Optionally, the aging time is 2 to 6 days.

[0016] Optionally, the mud material is any one of carbon mud, oil mud, and printing and dyeing sludge.

[0017] Optionally, the volume ratio of the landfill leachate to the phosphogypsum leachate is (0.4~1.2):1.

[0018] Optionally, the hydrothermal reaction temperature is 160-320° C., and the hydrothermal reaction time is 0.5-4.5 hours.

[0019] Optionally, the carbonization temperature is 450-850° C., and the carbonization time is 0.5-3.5 hours.

[0020] Another aspect of the present disclosure provides a waste liquid purification material, which is prepared by the method described above.

[0021] The present disclosure proposes a method for preparing a waste liquid purification material using electrolytic manganese slag and phosphogypsum leachate and a waste liquid purification material. The method comprises: mixing electrolytic manganese slag and iron-containing solid waste, stirring evenly, and obtaining an iron-manganese slag material; mixing the iron-manganese slag material with fly ash and mud, stirring evenly, granulating, and aging to obtain raw material particles; mixing garbage leachate and phosphogypsum leachate, stirring evenly, and obtaining a hydrothermal liquid; immersing the raw material particles in the hydrothermal liquid, performing a hydrothermal reaction, and taking out the solid part after the hydrothermal reaction to obtain an initial purification material; carbonizing the initial purification material, and obtaining a waste liquid purification material after the carbonization. The preparation process of the present disclosure is simple, and the required raw materials are all industrial wastes. The preparation of a new type of waste liquid purification material using electrolytic manganese slag and phosphogypsum leachate is realized through reasonable batching, hydrothermal reaction and carbonization activation. The prepared waste liquid purification material can not only efficiently adsorb and degrade high-concentration organic pollutants in the waste liquid, but also simultaneously remove heavy metal pollutants in the waste liquid. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1It is a flowchart of a method for preparing waste liquid purification material by using electrolytic manganese slag and phosphogypsum leachate according to a specific embodiment of the present disclosure;

[0023] Figure 2 The present invention is a schematic flow chart of a method for preparing waste liquid purification material by using electrolytic manganese slag and phosphogypsum leachate according to a specific embodiment of the present invention. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.

[0025] like Figure 1 and Figure 2 As shown, the present disclosure provides a method S100 for preparing a waste liquid purification material by using electrolytic manganese slag and phosphogypsum leachate, which specifically includes the following steps S110-S150:

[0026] S110, mixing the electrolytic manganese slag and the iron-containing solid waste, stirring evenly, to obtain ferromanganese slag material.

[0027] In some preferred embodiments, the mass ratio of electrolytic manganese slag to iron-containing solid waste is (15~75):100, for example, 15:100, 25:100, 35:100, 45:100, 55:100, 65:100, 75:100, etc. may be preferred.

[0028] It should be noted that electrolytic manganese slag mainly includes iron, manganese, aluminum, gypsum, silicate, calcium silicate, iron silicate, nitrate and other components (for example: SiO2, CaSO4·2H2O, CaSO4, FeS2, FeSiO3, Fe2O3, FeOOH, Fe3O4, (NH4)(Mn,Ca,Mg)PO4·H2O, (NH4)2SO4, MnSO4·H2O, MnCO3, Mn2O3, MnO2, Al4(OH)8(Si4O 10 )、Al2Mg4(OH) 12 (CO3)·3H2O and KAl(SO4)2·12H2O, etc.).

[0029] In other preferred embodiments, the iron-containing solid waste in this embodiment is any one of blast furnace gas mud, blast furnace gas ash, converter dust mud, electric furnace dust, and steel rolling dust mud, without specific limitation.

[0030] It should be further explained that the iron-containing solid waste in this embodiment mainly includes iron and ferrite components (for example, hematite, magnetite, pyrite, coke, ferrous oxide, metallic iron, zinc ferrite, etc.).

[0031] S120, mixing the iron-manganese slag with fly ash and mud, stirring evenly, granulating, aging, and obtaining raw material pellets.

[0032] In some preferred embodiments, the mass ratio of ferromanganese slag to fly ash and mud is (20-60):(15-45):100, for example, 20:15:100, 40:20:100, 60:45:100, etc.

[0033] In other preferred embodiments, the aging is allowed to stand for 2 to 6 days, for example, 2 days, 3 days, 4 days, 6 days, etc.

[0034] It should be noted that the mud material in this embodiment is any one of carbon mud, oil mud, and printing and dyeing sludge, which mainly includes components such as organic matter and inorganic salts (for example: kaolinite, hydromica, montmorillonite, mineral oil, surfactant, inorganic additive, alkylphenol polyoxyethylene ether, organic chlorine, phosphorus compounds, etc.).

[0035] It should be further explained that the fly ash of the present embodiment mainly includes components such as active aluminosilicates (for example, mullite, mica, garnet, epidote, ferrochlore, chalcanthite, etc.).

[0036] S130, mixing the landfill leachate and the phosphogypsum leachate, stirring evenly, and obtaining a hydrothermal solution.

[0037] In some preferred embodiments, the volume ratio of landfill leachate to phosphogypsum leachate is (0.4~1.2):1, for example, 0.4:1, 0.6:1, 0.8:1, 1.0:1, 1.2:1, etc.

[0038] It should be noted that landfill leachate mainly includes acidic substances, organic components, and mercury pollutants (for example: low molecular weight fatty acids, humus-like high molecular weight carbohydrates, medium molecular weight fulvic acid substances, ammonium ions, carbonate ions and sulfate ions, etc.).

[0039] It should be further explained that the phosphogypsum leachate of this embodiment mainly includes phosphate and gypsum components.

[0040] S140, immersing the raw material particles in the hydrothermal liquid to carry out a hydrothermal reaction, and after the hydrothermal reaction is completed, taking out the solid part to obtain an initial purified material.

[0041] In some preferred embodiments, the hydrothermal reaction temperature is 160~320℃, for example, 160℃, 200℃, 250℃, 300℃, 320℃, etc., and the hydrothermal reaction time is 0.5~4.5 hours, for example, 0.5 hour, 1 hour, 2 hours, 3 hours, 4 hours, 4.5 hours, etc.

[0042] S150, carbonizing the initial purification material, and obtaining the waste liquid purification material after carbonization.

[0043] In some preferred embodiments, the carbonization temperature is 450-850°C, for example, 450°C, 550°C, 650°C, 750°C, 850°C, etc., and the carbonization time is 0.5-3.5 hours, for example, 0.5 hours, 1.5 hours, 2.5 hours, 3.5 hours, etc.

[0044] In this embodiment, the reaction mechanism is as follows: during the aging process, the organic matter in the mud promotes the release of a small amount of iron and manganese in the iron-manganese slag, the active aluminosilicate in the fly ash adsorbs the organic matter in the mud, and adsorbs iron and manganese ions through ion exchange and charge balance, and at the same time, the active aluminosilicate in the fly ash also reacts with the gypsum, silicate, calcium silicate, iron silicate and other phases in the electrolytic manganese slag to stimulate geopolymerization and hydration mixing reaction, forming a gel to wrap the iron, manganese phases and mud. The inorganic salts and organic matter in the mud will also penetrate into the gel inclusions, thereby strengthening the hydration and hardening process of the colloid. The iron element and ferrite in the iron-containing solid waste coexist with the iron and manganese phases in the manganese slag to form a potential difference. Afterwards, by mixing the landfill leachate and the phosphogypsum leachate, the phosphate in the phosphogypsum leachate can neutralize some of the acidic substances in the landfill leachate and reduce its acidity, while the gypsum component in the phosphogypsum leachate adsorbs the organic matter in the landfill leachate. Afterwards, by immersing the raw material particles in the hydrothermal liquid, during the hydrothermal reaction, the phosphate in the hydrothermal liquid undergoes hydrolysis and polymerization and combines with the aluminum, iron minerals, aluminosilicates and gypsum in the raw material particles and the geological polymerization hydration mixed product to form calcium phosphate, iron phosphate, chlorohydroxyapatite, fluorohydroxyapatite, polyphosphate, calcium sulfonate, sulfide and mixed colloid coexisting and intermixing substances. Ammonia nitrogen substances and organic substances in the hydrothermal liquid are adsorbed and loaded on the surface and gaps of the mixed colloid. At the same time, under the hydrothermal effect, the nitrate in the electrolytic manganese slag reacts with the ammonia nitrogen substances in the hydrothermal liquid to generate nitrogen gas and is released, and the organic matter in the hydrothermal liquid is cracked into small molecular organic acids, thereby accelerating the dissolution and release of substances such as iron, manganese, aluminum, and calcium, and realizing the adsorption and stabilization of substances such as iron, manganese, aluminum, and calcium through complexation. The generated small molecular organic matter can also promote the reduction reaction of iron and manganese and intermix them together to form a complex mixed material system with multi-substance multi-directional intermixing and coexistence.

[0045] The preparation method disclosed in the present invention is simple, and the required raw materials are all industrial waste. Through reasonable batching, reasonable control of hydrothermal reaction and carbonization activation process, the new waste liquid purification material is prepared by using electrolytic manganese slag and phosphogypsum leachate. The prepared waste liquid purification material can not only efficiently adsorb and degrade high-concentration organic pollutants in the waste liquid, but also simultaneously remove heavy metal pollutants in the waste liquid.

[0046] The present disclosure not only reduces environmental pollution but also realizes high-value utilization of waste by converting electrolytic manganese slag and phosphogypsum leachate into waste liquid purification materials. This innovative research helps to promote the development of environmental protection technology, especially in the resource utilization of industrial waste slag and waste liquid, and provides new methods and technical routes. Therefore, the present disclosure uses electrolytic manganese slag and phosphogypsum leachate to prepare a new type of waste liquid purification material, which not only solves the problem of industrial waste slag treatment, but also provides a new solution for wastewater treatment, with significant environmental, economic and social benefits.

[0047] In another aspect of the present disclosure, a waste liquid purification material is provided. The waste liquid purification material is prepared by the method described above. For the specific process, please refer to the above description and will not be repeated here.

[0048] The waste liquid purification material obtained in this embodiment can be used to remove pollutants in waste liquid, for example, landfill leachate, or other waste liquids containing heavy metal pollution.

[0049] In some preferred embodiments, when the waste liquid purification material is applied to landfill leachate, the COD adsorption capacity of the landfill leachate is greater than 1835 mg / g, the ammonia nitrogen adsorption capacity is greater than 643 mg / g, the total phosphorus adsorption capacity is greater than 176 mg / g, and the mercury adsorption capacity is greater than 278 mg / g.

[0050] The following is a further description of the method for preparing waste liquid purification material using electrolytic manganese slag and phosphogypsum leachate in conjunction with specific examples:

[0051] The components of the landfill leachate, phosphogypsum storage leachate and electrolytic manganese slag used in the following embodiments are as follows:

[0052] Landfill leachate: The original landfill leachate was obtained from Zhuji Sanfeng Environmental Protection Energy Co., Ltd. The COD mass concentration of this batch of concentrated landfill leachate was 3639 mg / L, the total phosphorus concentration was 294 mg / L, and the ammonia nitrogen concentration was 1062 mg / L. 500 mg of mercury pollutant was dissolved in 1 L of the original landfill leachate to obtain the landfill leachate for the test.

[0053] Leachate from the phosphogypsum landfill: The leachate from the phosphogypsum landfill was sampled from the on-site collection pool at the phosphogypsum landfill in Xifeng County, Guizhou Province. The pH value was 2.23, the total phosphorus was 816 mg / L, the sulfate concentration was 2146 mg / L, the calcium ion concentration was 439.51 mg / L, the magnesium ion concentration was 564.89 mg / g, and the fluoride concentration was 91.37 mg / g.

[0054] Electrolytic manganese slag: The electrolytic manganese slag is taken from Guizhou Energy Mining Manganese Industry Group Co., Ltd., mainly including 23.52% SO3, 13.17% SiO2, 15.21% CaO, 13.09% Fe2O3, 6.82% Al2O3, 10.21% MnO, 2.96% K2O, 1.55% MgO, 0.86% TiO2 and other components (unavoidable impurities and ignition loss).

[0055] Example 1

[0056] This example takes the influence of the mass ratio of electrolytic manganese slag and iron-containing solid waste on the performance of the prepared waste liquid purification material as an example to illustrate the specific method includes the following steps:

[0057] Electrolytic manganese slag and iron-containing solid waste are mixed in a mass ratio of 7.5:100, 10:100, 12.5:100, 15:100, 45:100, 75:100, 80:100, 85:100, and 90:100, and stirred evenly to obtain iron-manganese slag, wherein the iron-containing solid waste is blast furnace gas mud. Iron-manganese slag, fly ash, and mud are mixed in a mass ratio of 20:15:100, stirred evenly, granulated, aged and left to stand for 2 days to obtain raw material particles, wherein the mud material is carbon mud. Mix the landfill leachate and phosphogypsum leachate in a volume ratio of 0.4:1, stir evenly, and obtain hydrothermal liquid. Immerse the raw material particles in the hydrothermal liquid, and then carry out a hydrothermal reaction. After the hydrothermal reaction, take out the solid part to obtain the initial purified material, wherein the hydrothermal reaction time is 0.5 hours and the hydrothermal temperature is 160°C. The initial purification material is carbonized, and a new type of waste liquid purification material is obtained after the carbonization is completed, wherein the carbonization temperature is 450° C. and the carbonization time is 0.5 hour.

[0058] Landfill leachate purification test: Weigh 1g of the new waste liquid purification material and add it to 1L of landfill leachate. Stir continuously for 30 minutes and centrifuge. The supernatant obtained is the purified liquid after treatment.

[0059] COD, ammonia nitrogen, total phosphorus, and mercury pollutant concentration detection: The chemical oxygen demand (COD) concentration in the solution is determined in accordance with the national standard "Determination of Chemical Oxygen Demand in Water Quality - Dichromate Method" (GB 11914-1989); the ammonia nitrogen concentration in the solution is determined in accordance with the "Determination of Ammonia Nitrogen in Water Quality - Salicylic Acid Spectrophotometric Method" (HJ536-2009); the total phosphorus concentration in the solution is determined in accordance with the standard "Determination of Phosphate and Total Phosphorus in Water Quality - Continuous Flow - Ammonium Molybdate Spectrophotometric Method" (HJ 670-2013). The dissolved mercury concentration in the solution is determined in accordance with the standard "Determination of Mercury, Arsenic, Selenium, Bismuth and Antimony in Water Quality - Atomic Fluorescence Method" (HJ 695-2014). The adsorption performance of adsorbents for COD, ammonia nitrogen, total phosphorus, and mercury pollutants is calculated according to formula (1), where: The pollutant adsorption capacity of the new waste liquid purification material is mg / g, and are the pollutant concentrations in the solution before and after the adsorption experiment in mg / L, V is the volume of the experimental leachate in L (1L), and m is the dosage of the new waste liquid purification material (1g).

[0060] (1)

[0061] The test results of the adsorption capacity of the new waste liquid purification material for COD, total phosphorus, ammonia nitrogen and mercury pollutants in this embodiment are shown in Table 1.

[0062] Table 1 Effect of the mass ratio of electrolytic manganese slag and iron-containing solid waste on the performance of the prepared waste liquid purification material

[0063]

[0064] It can be seen from Table 1 that when the mass ratio of electrolytic manganese slag to iron-containing solid waste is less than 15:100 (such as in Table 1, the mass ratio of electrolytic manganese slag to iron-containing solid waste = 12.5:100, 10:100, 7.5:100 and lower ratios not listed in Table 1), the electrolytic manganese slag is added less, and the electrolytic manganese slag and iron-containing solid waste react insufficiently, resulting in the adsorption capacity of the prepared new waste liquid purification material for COD, ammonia nitrogen, total phosphorus and mercury pollutants significantly decreasing with the decrease of the mass ratio of electrolytic manganese slag to iron-containing solid waste.

[0065] When the mass ratio of electrolytic manganese slag to iron-containing solid waste is equal to 15~75:100 (as in Table 1, the mass ratio of electrolytic manganese slag to iron-containing solid waste = 15:100, 45:100, 75:100), during the aging process, the organic matter in the mud promotes the release of a small amount of iron and manganese in the iron-manganese slag, and the active aluminosilicate in the fly ash adsorbs the organic matter in the mud, and adsorbs iron and manganese ions through ion exchange and charge balance. At the same time, the active aluminosilicate in the fly ash also reacts with the gypsum, silicate, calcium silicate, iron silicate and other phases in the electrolytic manganese slag to stimulate geopolymerization and hydration mixing reaction, forming a gel to wrap the iron, manganese phases and mud. The inorganic salts and organic matter in the mud will also penetrate into the gel inclusions, thereby strengthening the colloidal hydration and hardening process. The iron element and ferrite in the iron-containing solid waste coexist with the iron and manganese phases in the manganese slag to form a potential difference. Finally, the prepared new waste liquid purification materials have COD adsorption capacity greater than 1835 mg / g for leachate, ammonia nitrogen adsorption capacity greater than 643 mg / g, total phosphorus adsorption capacity greater than 176 mg / g, and mercury adsorption capacity greater than 278 mg / g.

[0066] When the mass ratio of electrolytic manganese slag to iron-containing solid waste is greater than 75:100 (as in Table 1, the mass ratio of electrolytic manganese slag to iron-containing solid waste = 80:100, 85:100, 90:100 and higher ratios not listed in Table 1), excessive addition of electrolytic manganese slag causes an imbalance in the material reaction, resulting in a significant decrease in the adsorption capacity of the prepared new waste liquid purification material for COD, ammonia nitrogen, total phosphorus and mercury pollutants as the mass ratio of electrolytic manganese slag to iron-containing solid waste further increases.

[0067] Therefore, in summary, considering the benefits and costs, when the mass ratio of electrolytic manganese slag to iron-containing solid waste is equal to 15~75:100, it is most conducive to improving the adsorption performance of the prepared new waste liquid purification material.

[0068] Example 2

[0069] This example takes the influence of the mass ratio of iron-manganese slag, fly ash and mud on the performance of the prepared waste liquid purification material as an example to illustrate the specific method including the following steps:

[0070] Electrolytic manganese slag and iron-containing solid waste are mixed in a mass ratio of 75:100 and stirred evenly to obtain iron-manganese slag, wherein the iron-containing solid waste is blast furnace gas ash. :45:100, 40:45:100, 60:45:100, 60:50:100, 60:55:100, 60:60:100, 65:45:100, 70:45:100, 75:45:100, mix iron-manganese slag, fly ash, and mud, stir evenly, granulate, age and stand for 4 days to obtain raw material particles, wherein the mud material is oil sludge. Mix the landfill leachate and phosphogypsum leachate in a volume ratio of 0.8:1, stir evenly, and obtain hydrothermal liquid. Immerse the raw material particles in the hydrothermal liquid, and then carry out a hydrothermal reaction. After the hydrothermal reaction is completed, take out the solid part to obtain the initial purified material, wherein the hydrothermal reaction time is 25 hours, and the hydrothermal temperature is 240°C. Carbonize the initial purified material, and after the carbonization is completed, obtain a new type of waste liquid purification material, wherein the carbonization temperature is 650°C, and the carbonization time is 2 hours.

[0071] The landfill leachate purification test, COD, ammonia nitrogen, total phosphorus, mercury pollutant concentration detection and corresponding adsorption capacity calculation are all the same as in Example 1. The adsorption capacity detection results of the new waste liquid purification material for COD, total phosphorus, ammonia nitrogen and mercury pollutants in this example are shown in Table 2.

[0072] Table 2 Effect of the mass ratio of iron-manganese slag, fly ash and mud on the performance of the prepared waste liquid purification material

[0073]

[0074] It can be seen from Table 2 that when the mass ratio of ferromanganese slag, fly ash and mud is less than 20:15:100 (such as in Table 2, the mass ratio of ferromanganese slag, fly ash and mud = 20:12.5:100, 20:10:100, 20:7.5:100, 15:15:100, 10:15:100, 5:15:100 and lower ratios not listed in Table 2), less ferromanganese slag and fly ash are added, and the reaction of ferromanganese slag, fly ash and mud is insufficient, resulting in the adsorption capacity of the prepared new waste liquid purification material for COD, ammonia nitrogen, total phosphorus and mercury pollutants being significantly reduced as the mass ratio of ferromanganese slag, fly ash and mud decreases.

[0075] When the mass ratio of ferromanganese slag, fly ash and mud is equal to 20~60:15~45:100 (as in Table 2, the mass ratio of ferromanganese slag, fly ash and mud is 20:15:100, 40:15:100, 60:15:100, 20:30:100, 40:30:100, 60:30:100, 20:45:100, 40:45:100 and 60:45:100), during the aging process, the organic matter in the mud promotes the release of a small amount of iron and manganese in the ferromanganese slag, and the active aluminosilicate in the fly ash absorbs the organic matter in the mud and absorbs iron and manganese ions through ion exchange and charge balance. At the same time, the active aluminosilicate in the fly ash also reacts with the gypsum, silicic acid, calcium silicate, iron silicate and other phases in the electrolytic manganese slag to stimulate geopolymerization and hydration mixing reaction to form a gel that wraps the iron, manganese phases and mud. Inorganic salts and organic matter in the mud will also penetrate into the gel inclusions, thereby strengthening the hydration and hardening process of the colloid. The iron and ferrite in the iron-containing solid waste coexist with the iron and manganese in the manganese slag to form a potential difference. Finally, the prepared new waste liquid purification materials have an adsorption capacity of COD greater than 1966 mg / g for leachate, an adsorption capacity of ammonia nitrogen greater than 712 mg / g, an adsorption capacity of total phosphorus greater than 198 mg / g, and an adsorption capacity of mercury greater than 314 mg / g.

[0076] When the mass ratio of ferromanganese slag, fly ash and mud is greater than 60:45:100 (as in Table 2, the mass ratio of ferromanganese slag, fly ash and mud = 60:50:100, 60:55:100, 60:60:100, 65:45:100, 70:45:100, 75:45:100 and higher ratios not listed in Table 2), ferromanganese slag and fly ash are added in excess, and the material reaction is unbalanced, resulting in the adsorption capacity of the prepared new waste liquid purification material for COD, ammonia nitrogen, total phosphorus and mercury pollutants being significantly reduced as the mass ratio of ferromanganese slag, fly ash and mud further increases.

[0077] Therefore, in general, considering the benefits and costs, when the mass ratio of iron-manganese slag, fly ash and mud is equal to 20~60:15~45:100, it is most conducive to improving the adsorption performance of the prepared new waste liquid purification material.

[0078] Example 3

[0079] This example takes the influence of the volume ratio of landfill leachate and phosphogypsum leachate on the performance of the prepared waste liquid purification material as an example to illustrate the specific method including the following steps:

[0080] Electrolytic manganese slag and iron-containing solid waste are mixed in a mass ratio of 75:100, stirred evenly, and iron-manganese slag is obtained, wherein the iron-containing solid waste is converter dust mud. Iron-manganese slag, fly ash, and mud are mixed in a mass ratio of 60:45:100, stirred evenly, granulated, aged and left to stand for 6 days to obtain raw material particles, wherein the mud material is printing and dyeing sludge. Garbage leachate and phosphogypsum leachate are mixed in a volume ratio of 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.8:1, 1.2:1, 1.4:1, 1.6:1, and 1.8:1, stirred evenly, and hydrothermal liquid is obtained. The raw material particles are immersed in the hydrothermal liquid, and then a hydrothermal reaction is carried out. After the hydrothermal reaction is completed, the solid part is taken out to obtain the initial purified material, wherein the hydrothermal reaction time is 4.5 hours and the hydrothermal temperature is 320°C. The initial purification material is carbonized, and a new type of waste liquid purification material is obtained after the carbonization is completed, wherein the carbonization temperature is 850° C. and the carbonization time is 3.5 hours.

[0081] The landfill leachate purification test, COD, ammonia nitrogen, total phosphorus, mercury pollutant concentration detection and corresponding adsorption capacity calculation are all the same as in Example 1. The adsorption capacity detection results of the new waste liquid purification material for COD, total phosphorus, ammonia nitrogen and mercury pollutants in this example are shown in Table 3.

[0082] Table 3 Effect of the volume ratio of landfill leachate and phosphogypsum leachate on the performance of the prepared waste liquid purification material

[0083]

[0084] It can be seen from Table 3 that when the volume ratio of landfill leachate to phosphogypsum leachate is less than 0.4:1 (such as in Table 3, the volume ratio of landfill leachate to phosphogypsum leachate = 0.35:1, 0.3:1, 0.25:1 and lower ratios not listed in Table 3), less landfill leachate is added, and the prepared hydrothermal liquid does not react fully with other materials during the hydrothermal reaction, resulting in the prepared new waste liquid purification material The adsorption capacity of COD, ammonia nitrogen, total phosphorus and mercury pollutants is significantly reduced as the volume ratio of landfill leachate to phosphogypsum leachate decreases.

[0085] When the volume ratio of landfill leachate to phosphogypsum leachate is equal to 0.4~1.2:1 (as shown in Table 3, the volume ratio of landfill leachate to phosphogypsum leachate = 0.4:1, 0.8:1, 1.2:1), the landfill leachate and phosphogypsum leachate are mixed, and the phosphate in the phosphogypsum leachate can neutralize some of the acidic substances in the landfill leachate and reduce its acidity. At the same time, the gypsum component in the phosphogypsum leachate absorbs the organic matter in the landfill leachate. The raw material particles are immersed in the hydrothermal liquid. During the hydrothermal reaction, the phosphate in the hydrothermal liquid undergoes hydrolysis and polymerization and combines with the aluminum, iron minerals, aluminosilicates and gypsum in the raw material particles and the geopolymerization hydration mixed product to form calcium phosphate, iron phosphate, chlorohydroxyapatite, fluorohydroxyapatite, polyphosphate, ettringite, sulfide and mixed colloids. Ammonia nitrogen substances and organic substances in the hydrothermal liquid are adsorbed and loaded on the surface and voids of the mixed colloid. At the same time, under the hydrothermal effect, the nitrate in the electrolytic manganese slag reacts with the ammonia nitrogen in the hydrothermal liquid to generate nitrogen gas and be released, while the organic matter in the hydrothermal liquid is broken down into small molecular organic acids, thereby accelerating the dissolution and release of substances such as iron, manganese, aluminum, and calcium, and achieving the adsorption and stabilization of substances such as iron, manganese, aluminum, and calcium through complexation. The generated small molecular organic matter can also promote the reduction reaction of iron and manganese and combine with each other to form a complex mixed material system with multi-substance multi-directional coexistence. Finally, the prepared new waste liquid purification material has an adsorption capacity of more than 2163 mg / g for COD of landfill leachate, more than 834 mg / g for ammonia nitrogen, more than 231 mg / g for total phosphorus, and more than 364 mg / g for mercury.

[0086] When the volume ratio of landfill leachate to phosphogypsum leachate is greater than 1.2:1 (such as in Table 3, the volume ratio of landfill leachate to phosphogypsum leachate = 1.4:1, 1.6:1, 1.8:1 and higher ratios not listed in Table 3), excessive addition of landfill leachate causes an imbalance in the material reaction during the hydrothermal reaction, resulting in a significant decrease in the adsorption capacity of the prepared new waste liquid purification material for COD, ammonia nitrogen, total phosphorus and mercury pollutants as the volume ratio of landfill leachate to phosphogypsum leachate further increases.

[0087] Therefore, in summary, considering the benefits and costs, when the volume ratio of landfill leachate to phosphogypsum leachate is equal to 0.4~1.2:10, it is most conducive to improving the adsorption performance of the prepared new waste liquid purification material.

[0088] Example 4

[0089] This example takes the effect of iron-containing solid waste on the performance of the prepared waste liquid purification material as an example to illustrate the specific method, which includes the following steps:

[0090] Electrolytic manganese slag and iron-containing solid waste are mixed in a mass ratio of 75:100, stirred evenly, and iron-manganese slag is obtained, wherein the iron-containing solid waste is any one of blast furnace gas mud, blast furnace gas ash, converter dust mud, electric furnace dust, and steel rolling dust mud. Iron-manganese slag, fly ash, and mud are mixed in a mass ratio of 60:45:100, stirred evenly, granulated, aged and left to stand for 6 days to obtain raw material particles, wherein the mud material is printing and dyeing sludge. Mix the landfill leachate and phosphogypsum leachate in a volume ratio of 1.2:1, stir evenly, and obtain hydrothermal liquid. Immerse the raw material particles in the hydrothermal liquid, and then carry out a hydrothermal reaction. After the hydrothermal reaction, take out the solid part to obtain the initial purification material, wherein the hydrothermal reaction time is 4.5 hours and the hydrothermal temperature is 320°C. Carbonize the initial purification material, and after the carbonization, obtain a new waste liquid purification material, wherein the carbonization temperature is 850°C and the carbonization time is 3.5 hours.

[0091] The landfill leachate purification test, COD, ammonia nitrogen, total phosphorus, mercury pollutant concentration detection and corresponding adsorption capacity calculation are all the same as in Example 1. The adsorption capacity detection results of the new waste liquid purification material for COD, total phosphorus, ammonia nitrogen and mercury pollutants in this example are shown in Table 4.

[0092] Table 4 Effect of iron-containing solid waste on the performance of the prepared waste liquid purification material

[0093]

[0094] It can be seen from Table 4 that when the iron-containing solid waste is any one of blast furnace gas mud, blast furnace gas ash, converter dust mud, electric furnace dust, and steel rolling dust mud, there is no significant difference in the adsorption capacity of COD, total phosphorus, ammonia nitrogen and mercury pollutants achieved by the prepared waste liquid purification material.

[0095] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present disclosure, but the present disclosure is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and substance of the present disclosure, and these modifications and improvements are also considered to be within the scope of protection of the present disclosure.

Claims

1. A method for preparing waste liquid purification materials using electrolytic manganese slag and phosphogypsum leachate, characterized in that: The method comprises: The electrolytic manganese slag and the iron-containing solid waste are mixed and stirred evenly to obtain an iron-manganese slag material; The iron-manganese slag is mixed with fly ash and mud, stirred evenly, granulated, aged, and raw material pellets are obtained; the mud includes organic matter and inorganic salts; The landfill leachate and the phosphogypsum leachate are mixed and stirred evenly to obtain a hydrothermal solution; Immersing the raw material particles in the hydrothermal liquid to perform a hydrothermal reaction, and after the hydrothermal reaction is completed, taking out the solid part to obtain an initial purified material; The initial purification material is carbonized to obtain a waste liquid purification material.

2. The method according to claim 1, characterized in that The mass ratio of the electrolytic manganese slag to the iron-containing solid waste is (15-75):

100.

3. The method according to claim 1, characterized in that The iron-containing solid waste is any one of blast furnace gas mud, blast furnace gas ash, converter dust mud, electric furnace dust, and steel rolling dust mud.

4. The method according to claim 1, characterized in that: The mass ratio of the ferromanganese slag material to the fly ash and the mud material is (20-60):(15-45):

100.

5. The method according to claim 1, characterized in that The aging time is 2 to 6 days.

6. The method according to claim 1, characterized in that The mud material is any one of carbon mud, oil mud and printing and dyeing sludge.

7. The method according to claim 1, characterized in that The volume ratio of the landfill leachate to the phosphogypsum leachate is (0.4~1.2):

1.

8. The method according to claim 1, characterized in that The hydrothermal reaction temperature is 160-320° C., and the hydrothermal reaction time is 0.5-4.5 hours.

9. The method according to claim 1, characterized in that: The carbonization temperature is 450-850° C., and the carbonization time is 0.5-3.5 hours.

10. A waste liquid purification material, characterized in that: The waste liquid purification material is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for synergistically and harmlessly treating electrolytic manganese residue leachate and ardealite leachate

    CN117776355A

  • Method for preparing adsorbent from landfill leachate and red mud as well as product and application thereof

    CN117960110A